THE READINESS OF A FUTURE TEACHER-PSYCHOLOGIST TO ENGAGING ADOLESCENTS INTO PROJECT-RESEARCH ACTIVITIES: A CORRELATIONAL ASPECT - Курманбекова, Маншук; Абдуллаева, Гульзира; Хан , Наталья (Pedagogy and Psychology, 2022)
The article presents the results of diagnostics of future teacher-psychologist's readiness to involving teenagers into project-research activities. The research was taken on the basis of Abai Kazakh National Pedagogical University and Aktobe Regional University named after K. Zhubanov, in which 119 third- and fourth-year students of "Pedagogy and Psychology" direction took part, by using a set of diagnostic methods, corresponding to the criteria of the indicated readiness. The obtained results allowed to substantiate the relationship between the readiness of modern adolescents for project-research activities and the studied readiness of future teachers-psychologists.